PEMELIHARAAN IKAN GURAME (OSPHRONEMUS GOURAMY) DENGAN PEMBERIAN PAKAN YANG BERBEDA DALAM WADAH AKUARIUM - Nasya Salsabila Aurilia; Evi Liviawaty, Nurhsahbani Komarudin, Kenny Pramudya Hermanto (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Gourami fish is a type of freshwater fish that is popular as a food fish in Southeast Asia and South Asia. Apart from that, gourami are also often kept in aquariums. Apart from being known as gurami, this fish also has several local names such as gurami. In maintenance, one of the important factors in raising fish is the feed factor, whether artificial feed or natural feed, so it is very determining in the growth and development of fish, if the feed given is sufficient and of good quality it will really help growth, and improve The body's immune system is resistant to attacks by disease or parasites. Likewise, the type of feed given plays a very important role in determining the quality of the fish. The quality and quantity of feed is very important in fish growth, because only with good feed can fish grow and develop according to what we want. Good quality feed is feed that has balanced nutrition, including protein, carbohydrates and fats as well as vitamins and minerals. Because gourami fish are omnivorous, the food given can be in the form of leaves or pellets. Gourami fish (Osphronemus gouramy) is the main product of freshwater fish cultivation. Apart from being able to reproduce naturally and being easy to maintain, this fish is also a freshwater fish with economic value. Apart from its advantages, there are also obstacles in keeping fish that are often faced, usually gourami are slow to grow, so they need to pay attention to their maintenance. Factors that influence the growth rate are less intensive maintenance and feeding that does not support the growth of fish in the aquarium container